STRATEGI PENGEMBANGAN DESA WISATA PESISIR DI DESA TAMBAKREJO KABUPATEN MALANG - Pamela Dinar Rahma; Rifky Aldila Primasworo (Universitas Tribhuwana Tunggadewi Malang, 2018)
Tambakrejo Village is one of the coastal villages in southern Malang Regency that has the potential of beach beauty and fishery products are quite abundant. These potentials include Tamban Beach, Sendiki Beach, Asmara Bay Beach, Sendangbiru Beach, Sempu Island, and Pick Up Ceremony. Tambakrejo Village is included in 13 (thirteen) villages that will be developed as a tourist village by the Government of Malang Regency. The purpose of this research is to know the characteristics of Tambakrejo Village related to the development of tourist village, to know the potential and the problems, and to determine the strategy of development of Tambakrejo Village. The type of this research is descriptive - evaluative by using method of qualitative and quantitative analysis. Tambakrejo village is a coastal village with moderate topography, and the soil type is alluvial soil and litosol. The potentials of Tambakrejo Village are, among others, the potential of nature, cultural potential, diversity of marine products, accessibility to good villages, adequate tourism facilities, still have vacant land for development, and the beauty of the tourist attraction in Tambakrejo Village is well known by community. While the problems associated with the garbage and accessibility that there are some road networks that need improvement. The Tambakrejo Village development strategy is to optimize the attractive landscape conditions, the quality and diversity of commodities, increase the diversity of tourist attractions, improve facilities, facilities and facilities, and utilize the availability of local labor.